Simulation of Tunnel Excavations in Squeezing Ground - Hanafy, Ahmed Dia Eldin (My University, 1981)
Empirical, analytical, and semi-rational methods for the stability analysis and design of underground openings are generally not adequate to consider the major design parameters for tunnels in squeezing ground. Tunnel construction in squeezing ground and the increasing North American use of the precast concrete segmental liners were the prime motivation for developing an elastic-plastic-creep simulation of tunnel excavation and liner placement.
Based on the finite element method, the simulation method incoporates: the primary state of stress; excavation in stages; liner placement delay; and determination of the elastic-plastic-creep response for each stage of construction, including ground-interface-support system interaction for both plane strain (two-dimensional) and advancing face (three-dimensional) conditions. Construction sequences of excavation and support placement are simulated using 'deactivation' and 'reactivation' operations on the stiffness matrix terms corresponding to the selected rate of face advance. Incorporation of the inelastic behaviour of both ground yielding and time-dependent deformations is based on the initial stress and initial strain methods, respectively. The three-dimensional stress analysis near the advancing face is based on an axisymmetric approach and Fourier series approximation that allows the non-symmetric radial and axial loadings due to the primary state of stress to be considered. The axisymmetric approach is also extended to include inelastic ground behaviour.
A comprehensive design for a tunnel in a formation that may exhibit squeezing is given. Using this typical field problem, several parametric studies are presented. It is shown that the elastic deformations are only significant near the advancing face and their influence is very minor at a distance of about two times the tunnel diameter. The consideration of the actual advancing face condition, lining placement delay, and the use of a soft backing can significantly reduce the design stresses developed in the liner.
The simulation method presented can be used to develop improved ground characterization through the monitoring of tunnel convergence followed by back analysis.
Keywords: Civil Engineering; Civil Engineering